Numerical analysis of ionized fields associated with HVDC transmission lines including effect of wind - Li, Xin (2007)
Corona discharges on the conductor surface of a HVDC transmission line generate ion flow in the interelectrode space, and therefore cause power losses as well as environmental concerns. To evaluate these effects, one has to solve the i n flow field (or ionized field). However, the solution of this problem is very difficult due to its nonlinearity and the effect of wind. Although this problem has been tackled by a number of researchers over the past several decades, a review of the existing literature indicates that problems associated with strong wind or bundled lines are still not solved satisfactorily. This thesis presents two new numerical algorithms, the FEM based optimization algorithm and the upwind FVM (node-centered FVM and triangular FVM) based relaxation algorithm, for solving unipolar ionized fields including the effect of wind. The validity and efficiency of the presented algorithms is favorably demonstrated on a coaxial cylindrical configuration and on a unipolar line model in the presence of wind. Stable and fast convergence is observed for the former algorithm under moderate wind conditions, while excellent iterative behavior is exhibited by the latter with wind velocities in the range from 0 to 45 m/s or even higher. The FVM based relaxation algorithm is also extended to analyze the bipolar ionized field. A simplified model is suggested so that the bipolar ionized field in the absence of wind may be treated as the combination of two unipolar ionized fields for computing the field quantities at ground level. The ionized field due to bundled unipolar DC lines is investigated in detail by using the FVM based relaxation algorithm. The geometries considered are typical of practical DC lines and the effect of wind is included. The validity of the equivalent single conductor approach is verified.